Chryseobacterium phosphatilyticum sp. nov., a phosphate-solubilizing endophyte isolated from cucumber (Cucumis sativus L.) root. Issue 3 (29th November 2018) - Jeong, Jin-Ju; Sang, Mee Kyung; Lee, Dong Wan; Choi, In-Geol; Kim, Ki Deok
Abstract : A bacterial strain, designated as ISE14 T, with Gram-stain-negative and non-motile rod-shaped cells, was isolated from the root of a cucumber plant collected in a field in Iksan, Republic of Korea and was characterized using a polyphasic approach. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain ISE14 T represented a member of the genus Chryseobacterium and was closely related to Chryseobacterium viscerum 687B-08 T (16S rRNA gene sequence similarity of 98.50 %), Chryseobacterium lactis NCTC 11390 T (98.49 %), Chryseobacterium ureilyticum F-Fue-04IIIaaaa T (98.49 %) and Chryseobacterium oncorhynchi 701B-08 T (98.04 %). Average nucleotide identity values between genome sequences of strain ISE14 T and the closely related species ranged from 81.44 to 83.15 %,  which were lower than the threshold of 95 % (corresponding to a DNA–DNA hybridization value of 70 %). The DNA G+C content of strain ISE14 T was 36.3 mol%. The dominant fatty acids were iso-C15 : 0, summed feature 9 (iso-C17 : 1 ω 9 c and/or C16 : 0 10-methyl), summed feature 3 (iso-C15 : 0 2-OH and/or C16 : 1 ω7 c ) and iso-C17 : 0 3-OH. The major polar lipids were phosphatidylethanolamine, three unidentified aminolipids and eight unidentified lipids; the predominant respiratory quinone was MK-6. On the basis of the evidence presented in this study, strain ISE14 T can be distinguished from closely related species belonging to the genus Chryseobacterium . Thus, strain ISE14 T is a novel species of the genus Chryseobacterium, for which the name Chryseobacterium phosphatilyticum sp. nov. is proposed. The type strain is ISE14 T (=KACC 19820 T =JCM 32876 T ).